Business Collaboration on Innovation, as Exemplified by the Service Sector - Węgrzyn, Grażyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article identifies differences in enterprises’ collaboration on innovation across the European Union. The first part explains the concept of innovative activity of business and examines the percentage of enterprises actively pursuing innovation in individual EU countries. The next part describes the methods of collaboration on innovation employed by enterprises in the service sector, by selected groups of partner institutions. Service providers located in countries classified as innovation leaders have much closer collaboration on innovation with their partner institutions than those located in countries with low or moderate innovation levels. What seems particularly important for any economy’s innovation level is the collaboration of service providers with the suppliers of equipment, materials, components and software (Denmark, the Netherlands), with their clients from the private sector (Finland, Sweden) and with universities (Germany).